(untitled) (Jurnal Teknologi (Sciences & Engineering), 2021)
Poikilospermum suaveolens is a plant could grows in the limestone area in Maros, Indonesia. The leaves are generally widely used as traditional medicine for treatment of wounds by local communities. This study aims to examine the wound healing potential of P. suaveolens leaves extract as well as scientific clarify of the plant. The plant leaves were extracted by maceration. The measurement of antioxidant activity by the DPPH technique (1,1 diphenil-2-pikrilhidrazil) spectrophotometrically. The antimicrobial activity was evaluated by formation of the inhibition zone. The wound healing activity was performed the percentage of injury closure in rats skin injury. The antioxidant activity showed that 70% ethanol and ethyl acetate extracts were not significantly different, however, highly distinct to the positive control (Butylated Hidroxyanisole). The antimicrobial activity of extract showed 70% ethanol and ethyl acetate extracts were not significantly against Staphylococcus aureus and Candida albicans, but significantly against Pseudomonas aeruginosa. The evaluation of P. suaveolens extract on the rate of wound closure activity quickly, i.e., within 15 days the injury on the test animal was recovered. This study concludes that the P. suaveolens plant extracts are potential as a sources of active substances for wound healing.